MEASURING THE PROPENSITY FOR BUILDING SOCIAL CAPITAL DEPENDING ON TIES-STRENGTH - Zabłocka, Agata; Praszkier, Ryszard; Petrushak, Ewa; Kacprzyk-Murawska, Marta (Journal of Positive Management, 2017)
Purpose: This paper is addressing the question what personal characteristics help a leader to build social capital. The purpose is to present the development of a questionnaire to measure leaders’ propensity for building social capital, depending on the perceived strength of bonds; it is also aimed at presenting the preliminary results of intercultural studies. Design/methodology/approach: This paper starts with a review of the theory on social capital and Granovetter’s concept of the “strength of weak ties.” Next the process of the development of the related questionnaire is presented. Findings: The developed questionnaire is a universal and reliable tool that can be used to study various social problems in different populations. The preliminary results of the questionnaire from 10 European countries suggest that the more distant the relationship is perceived the lower is the level of trust and sense of support. Moreover, data suggest that socio-economic organizations as well as those which are longer on the market obtained the highest results on the questionnaire’s scales. Social implications: In conclusion possible applications are discussed, including measuring the dynamics of change in individuals’ preparedness to build social capital, depending on the social or political context, for example, the presumable “openness” during peaceful social activities or movements. Originality/value: Social capital is commonly seen as a positive value, both in its individual and group dimensions, and several tools exist for measuring both. However, there seems to be a void and a need for a questionnaire measuring individual’s propensity to develop social capital.